2009
DOI: 10.1111/j.1600-048x.2009.04687.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive hybridization in a contact zone between MacGillivray's warblersOporornistolmieiand mourning warblersO. philadelphiadetected using molecular and morphological analyses

Abstract: There are many pairs of related western and eastern avian taxa in North America, and for many of these, little is known about their interactions in sympatry. One example is provided by MacGillivray's warblers Oporornis tolmiei and mourning warblers Oporornis philadelphia. There have been occasional reports of range contact and hybridization between these forms, but recent authors have doubted these reports. We show that these two species do in fact come into extensive range contact in the southern Peace Region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 44 publications
(74 reference statements)
1
41
0
Order By: Relevance
“…A large combination of marker types may be needed to identify individuals with introgressed DNA (Väli et al 2010b). Hybrid zones are often "tension zones" in which selection acts against the neutral diffusion of alleles across species (e.g., Kvist and Rytkönen 2006;Carling and Brumfield 2008;Gay et al 2008Gay et al , 2009Irwin et al 2009a;Mettler and Spellman 2009). Given constant ecological or reproductive conditions, a hybrid zone can be constrained to a narrow width by this mechanism, preserving the genetic integrity of the species on either side.…”
Section: Classical Introgression Across a Hybrid Zonementioning
confidence: 99%
“…A large combination of marker types may be needed to identify individuals with introgressed DNA (Väli et al 2010b). Hybrid zones are often "tension zones" in which selection acts against the neutral diffusion of alleles across species (e.g., Kvist and Rytkönen 2006;Carling and Brumfield 2008;Gay et al 2008Gay et al , 2009Irwin et al 2009a;Mettler and Spellman 2009). Given constant ecological or reproductive conditions, a hybrid zone can be constrained to a narrow width by this mechanism, preserving the genetic integrity of the species on either side.…”
Section: Classical Introgression Across a Hybrid Zonementioning
confidence: 99%
“…Hybrid zones can be relatively wide and dominated by morphological and genetic intergrades between the parental taxa (e.g., Sibley and Short 1964, Irwin et al 2009, Vallender et al 2009, Den Hartog et al 2010, or relatively narrow and dominated by individuals that are morphologically and genetically close to the parental taxa (e.g., Barrowclough et al 2005, Leafloor et al 2013. At the possible extreme, one study found little evidence for interbreeding between two sympatric and closely-related passerine species, and possible hybridization only can be speculated (Toews and Irwin 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Variance in cline width has been used to infer selection coefficients associated with particular characters (Barton & Hewitt 1985). The majority of avian hybrid zones studied thus far exhibit cline widths of 100-1000 km (Barrowclough 1980, Rohwer et al 2001, Irwin et al 2009, Mettler & Spellman 2009. Case examples of narrow avian hybrid zones with cline widths of 10-100 km have been documented in manakins (Brumfield et al 2001), wrens (Selander 1965), crows (Meise 1928), titmice (Curry & Patten 2014), warblers (Toews et al 2011), and grackles (Yang & Selander 1968).…”
Section: Discussionmentioning
confidence: 99%